The Right to Work and Differentiation in Indian Employment - Wendy Olsen and Smita Mehta (Indian Journal of Labour Economics, Sept/Oct. 2006, 2006)
The spread of the `right to work' notion reflects in part a pattern of globalisation which goes beyond the economic to the ideological and ethical domains. The paper aims to clarify the ethical basis of the right to work in India. We compare the right to work with the rights of citizens, specifying three types of rights (procedural rights; substantive rights which are opportunities; and substantive rights to functioning). Therefore, the outcomes of different forms of work need to be measured. The levels of remuneration and the terms & conditions of work - including unpaid work - have to be looked at empirically. The right to work is not just a theoretical question nor a simple matter of principle. We present evidence of the diversity of working practices in India using NSS data from 1999. We describe gender variation and state-wise as well as religion-based variation. Based on our unique findings, which cover extra-domestic work and introduce a very narrow definition of `inactivity', we argue that the right to decent work has different implications for differently-placed people. Simple answers like a universal right to paid work are insufficiently specified. Having a discourse about the right to work is much better than having a neoliberal discourse about `employability'. The paper reviews how `work' took place in the Indian economy in 1999 and how poverty, gender, and the right to decent work interact.